ANALISIS PENGALAMAN PENGGUNA LAZADA DAN BUKALAPAKDENGAN MENERAPKAN METODE USER EXPERIENCE QUESTIONNAIRE - Fenny Purwani; Erin Aryanti; Koiriah Maula Nanda; Resa Ayu Sari; Dina Olyvia (Jurnal Riset Teknik Komputer, 2024)
The rapid growth of e-commerce in Indonesia, with platforms like Lazada and Bukalapak, has made User Experience (UX) a critical factor for success. This study aims to analyze and compare the UX of both applications using the User Experience Questionnaire (UEQ) method, which evaluates six dimensions: attractiveness, clarity, efficiency, dependability, stimulation, and novelty. A quantitative approach was applied, using a questionnaire distributed to 180 respondents aged 17-30 years. The results show that both applications received positive overall evaluations, with Lazada outperforming in terms of efficiency. These findings provide essential recommendations for developers to enhance the UX of e-commerce platforms.